Microbial Assessment of Herbal Cleansers (Bitters) Sold in Ota, Ogun State, Nigeria - O. O., Ayepola; U. H., Ugboko; B. O., Abu; S. J., Olorunshola (Covenant Journal of Physical and Life Sciences, 2018)
The use of herbal medicines is on an increasing trend globally. Herbal medicines may be beneficial but are not completely harmless due to deficient quality control in certain cases. This study evaluated the microbial content of some herbal cleansers (bitters). Eight herbal cleansers obtained from pharmacies in Ota were evaluated for their microbial content. Bacterial and fungal isolates identified from the samples include Bacillus subtilis, Staphylococcus aureus, Staphylococcus epidermidis, Lactobacillus spp., Proteus spp., Pseudomonas spp., Shigella spp., Aspergillus niger, Rhizopus spp., Geotrichum spp., Fusarium spp., Alternaria spp., Penicillium spp., Mucor spp., Diplosporium spp. and Trichothecium spp. The mean total aerobic plate count values of the herbal cleansers were in the range of 1.0x104 and 3.0x105 cfu/ml. The results of this study revealed the presence of certain pathogenic organisms in these formulations and this emphasizes the importance of having stringent quality control measures in the manufacture of herbal preparations.